ORGANIZING MARKETING ACTIVITIES IN SMALL BUSINESS AND BUSINESS SUBJECTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article discusses the features, conditions and principles for the development of the tourism services market, the priorities of state policy in the field of tourism, the role of regional tourism systems in the development of the tourism services market and the formation of a favorable competitive environment.